2000
DOI: 10.1038/79697
|View full text |Cite
|
Sign up to set email alerts
|

Metformin reverses fatty liver disease in obese, leptin-deficient mice

Abstract: There is no known treatment for fatty liver, a ubiquitous cause of chronic liver disease. However, because it is associated with hyperinsulinemia and insulin-resistance, insulin-sensitizing agents might be beneficial. To evaluate this possibility, insulin-resistant ob/ob mice with fatty livers were treated with metformin, an agent that improves hepatic insulin-resistance. Metformin improved fatty liver disease, reversing hepatomegaly, steatosis and aminotransferase abnormalities. The therapeutic mechanism like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
421
4
15

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 625 publications
(473 citation statements)
references
References 42 publications
33
421
4
15
Order By: Relevance
“…89 It has been shown that metformin reverses fatty liver disease in obese, leptin-deficient mice. 90 In 20 patients with NASH, 4 months of metformin treatment led to a reduction in serum transaminase (which were normalized in 50% of cases) and liver volume compared with no changes in non-compliant patients. 91 Clearly, a randomized controlled trial is urgently required to confirm these results.…”
Section: Drugs Improving Insulin Sensitivitymentioning
confidence: 97%
“…89 It has been shown that metformin reverses fatty liver disease in obese, leptin-deficient mice. 90 In 20 patients with NASH, 4 months of metformin treatment led to a reduction in serum transaminase (which were normalized in 50% of cases) and liver volume compared with no changes in non-compliant patients. 91 Clearly, a randomized controlled trial is urgently required to confirm these results.…”
Section: Drugs Improving Insulin Sensitivitymentioning
confidence: 97%
“…Metformin reduces fatty acid oxidation and stimulates aerobic metabolism and lactate production in preadipocytes. 4 In Ob/Ob mice, it increased relative expenditure of energy associated with decreased expression of uncoupling protein 2 (UCP-2) in hepatic tissue 5 resulting in reduced steatosis, aminotransferases, and hepatic tumor necrosis factor alpha (TNF-a) expression and improvement in IS. Metformin appears to be safe, with a single case report of acute hepatitis in a diabetic patient and no cases of lactic acidosis in NASH.…”
Section: Mode Of Actionmentioning
confidence: 99%
“…The biguanide, metformin, reduces hyperinsulinemia and improves hepatic insulin resistance. 79 It is beneficial in animal models of NASH, 79 but initial open-label studies in humans suggested only transient improvements in serum liver enzymes. 80 In two recent small randomized trials of non-diabetic patients with NAFLD, metformin treatment significantly improved serum aminotransferases compared to treatment with calorie and lipid restricted diets, 81 or vitamin E, 82 but in only one study did metformin significantly decrease liver fat, necro-inflammation and fibrosis.…”
Section: Diagnosing Fatty Livermentioning
confidence: 99%